Synchrony During Online Encounters Affects Social Affiliation and Theory of Mind but Not Empathy - Basile, Chiara; Lecce, Serena; van Vugt, Floris Tijmen (Frontiers in Psychology, 2022)
Moving together in time (synchronized) affects human social affiliation and cognition. However, it is unclear whether these effects hold for on-line video meetings and to whether they extend to empathy (understanding or sharing others' emotions) and theory of mind (ToM; attribution of mental states to others). 126 young adult participants met through online video in unacquainted pairs. Participants either performed 3 minutes of synchronous arm movements paced by sounds (n=40), asynchronous movements (n=46) or a small talk control condition (n=40). In a subsequent empathy task, participants were asked to talk about events from their lives. A recording of this conversation was played back and each participant rated, at predetermined time points, how they themselves and their partner felt. From this we calculated empathic accuracy (accuracy of the estimation of the other’s emotion) and emotional congruence (emotion sharing). ToM was measured by showing videos of geometrical shapes interacting and asking the participants to describe what happened, measuring the amount of intentionality. We found that participants in the synchrony condition rated feeling greater closeness and similarity to their partners relative to the asynchronous condition. Further, participants in the synchrony group tended to ascribe more intentionality to the abstract shapes than participants in asynchrony condition, suggesting greater theory of mind. Synchrony and asynchrony groups did not reliably differ in empathic accuracy nor emotional congruence. These results suggest that moving in synchrony has effect on social affiliation measures even in online encounters. These effects extend to ToM tendencies but not empathic accuracy or emotion sharing. These results highlight the potential of synchronous movement in online encounters to affect a subset of social cognition and affiliation measures.